HUBUNGAN PENGETAHUAN TENTANG COVID-19 DAN KETERSEDIAAN INFORMASI DENGAN TINGKAT KECEMASAN IBU HAMIL MELAKUKAN PEMERIKSAAN ANC (ANTENATAL CARE) DI PUSKESMAS MENDIK TAHUN 2021 - Zainal Arifin; Sri Winarni; Atik Mawarni; Cahya Tri Purnami (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2022)
The Covid-19 pandemic, which has been active in Indonesia since early March 2020, has become a serious threat to all groups, including pregnant women, who are at a high risk of contracting the COVID-19 virus, particularly to the fetus they are carrying. Pregnant women require continuous knowledge and information in order to avoid anxiety. The goal of this study was to see if there was a link between pregnant women's knowledge and availability of information and their level of anxiety when performing ANC (Antenatal care) examinations. Observational study using a cross-sectional approach. This study's population consisted of 169 pregnant women, with a sample of 61 pregnant women drawn using a simple random sampling method. The findings revealed that 82.0% of pregnant women aged 17-45 years old (Mean: 28.31 and SD: 5.9), did not work, 32.8% of pregnant women with good knowledge did not experience anxiety, and 31.1% of pregnant women did not experience anxiety. Knowledgeable pregnant women have mild anxiety, and 3.3% of knowledgeable pregnant women have moderate anxiety. The Spearmen Rank correlation test results revealed that there was no relationship between knowledge (p value = 0.641 r = 0.061) and information availability (p value = 0.582 r = -0.072) and the level of anxiety of pregnant women during ANC (Antenatal care) examinations at the Mendik Health Center. It is hoped that with good knowledge and sufficient information can filter the right information and recommended that pregnant women consult with health workers diligently in order to obtain knowledge and information about pregnancy services.